Coupling of the coagulation/flocculation and the anodic oxidation processes for the treatment of textile wastewater - Sourour Bouznif (IWA Publishing, 2021)
The increased demand for textile products leads to an increase in the quantity of wastewater discharged. It becomes indeed one of the most critical health and environmental problems in the world. The main challenge, therefore, is to develop innovative techniques for treating this wastewater with low production costs and better efficiency. The major objective of this work was to investigate the efficiency of the coupling of the coagulation–flocculation and the anodic oxidation processes on the platinum electrode in the removal of organic, mineral, and microbial pollution contained in textile effluents. A series of experiments is carried out on samples prepared in the laboratory, in which the textile effluent was mixed with a secondary effluent from an urban wastewater treatment plant. The treatment consists of two steps: a coagulation–flocculation process using aluminum salts as a coagulant and an anodic oxidation on the platinum electrode using photovoltaic panels for the production of electric current. The treatment at optimized conditions reveals that the coupling of the two processes made it possible to achieve satisfactory results. The abatement rates were 95.97% for the turbidity, 90% for COD, 100% for BOD, 100% for , 53.6% for , and 100% for . The coupling of the two processes ensured the complete elimination of fecal germs. Thanks to the satisfactory results, the obtained permeate can be reused in the dyeing process in the textile industry. HIGHLIGHTS Coupling of the coagulation–flocculation process with anodic oxidation allowed removing contaminants.; The coupling of the two processes ensured the complete elimination of fecal germs.; The total elimination of organic, nitrogen, and phosphorus pollution was obtained.; The treated water can be reused for different purposes.; Mixing urban wastewater with the textile effluent improves the pollutant removal rate.;